EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS PROYEK (PJBL)TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPTD SDN MORKEPEK - Ramanda Alex Pradana; Mulgias Salam; Ika Dia Rahmawati (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
The low learning outcomes of fourth-grade students at SDN Morkepek in Natural and Social Science, all of whom scored below the Learning Objective Attainment Criteria, highlight the need for more active and meaningful learning model innovations. This study aims to analyze the effectiveness of implementing the Project-Based Learning model on students' cognitive learning outcomes in Natural and Social Science within the context of the Merdeka Curriculum. This study employed a quantitative approach with a pre-experimental One Group Pretest-Posttest Design. The research subjects were 30 fourth-grade students at SDN Morkepek selected through purposive sampling. The research instrument consisted of 25 multiple-choice questions covering cognitive domains that had been tested for validity and reliability. Data analysis was conducted using the Paired Sample t-test and N-Gain score calculation. The results showed an increase in the average score from a pretest of 55.73 to a posttest of 80.83, with a difference of 25.10 points, and all students successfully exceeded the Learning Objective Attainment Criteria after the implementation of the Project-Based Learning model. The average N-Gain score of 0.57 falls into the moderate category, with 93.3 percent of students in the moderate category and 6.7 percent in the high category. Hypothesis testing showed a significant difference between learning outcomes before and after treatment, with a very large effect size. These findings imply that the Project-Based Learning model is effective as an active learning model and worthy of consistent integration in Natural and Social Science learning at the elementary school level within the Merdeka Curriculum implementation.